EKSEKUSI PUTUSAN PENGADILAN AGAMA YANG BELUM INKRACHT BERKENAAN DENGAN HAK ASUH ANAK - Chandra Darusman S; M. Ikhwan Adabi; Apri Rotin Djusfi; Phoenna Ath Thariq; Eza Aulia; Rahmat Jhowanda; Liza Agnesta Krisna (Arena Hukum, 2023)
Law Number 23 of 2002 concerning Child Protection emphasizes that in the event of separation due to divorce and other situations without eliminating the child's relationship with his parents, the child still has the right to meet and have permanent personal contact with both parents. However, the situation that occurs in society and the existence of a legal vacuum shows that often children cannot meet their parents who have been appointed as custodians because the divorce case decision has not yet become legally binding. This normative juridical research uses statutory approach and the conceptual approach. The concept of child protection regulated in the Child Protection Act and other laws and regulations also includes the protection of children in situations of parental household conflict and protection in situations where the legal process against parental household conflicts is still ongoing and has no permanent legal force. The researcher recommends a change to the Law on Religious Courts. In this case, it is necessary to add legal norms that stipulate those children must be handed over to parents who are holders of custody since the court decision is pronounced, or the issuance of a Supreme Court Rule as the legal basis for implementing execution.